2022
DOI: 10.1111/medu.15008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of specific learning difficulties on general practice written and clinical assessments

Abstract: Background: Substantial numbers of medical students and doctors have specific learning difficulties (SpLDs) and failure to accommodate their needs can disadvantage them academically. Evidence about how SpLDs affect performance during postgraduate general practice (GP) specialty training across the different licencing assessments is lacking. We aimed to investigate the performance of doctors with SpLDs across the range of licencing assessments.Methods: We adopted the social model of disability as a conceptual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Medical education is one of the most demanding training programs in both academic and emotional dimensions (1). Previous studies have reported higher rates of poor mental health among nursing students (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Medical education is one of the most demanding training programs in both academic and emotional dimensions (1). Previous studies have reported higher rates of poor mental health among nursing students (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…As the field of health professions education (HPE) shifts towards creating more equitable learning environments, researchers and educators have increasingly underscored the importance of equity in assessment processes. In a recent article published in Medical Education , Botan and colleagues 1 conducted a study on how specific learning difficulties (SpLDs) impact physicians' performance on various assessments. Their study sample included 2070 physicians, of whom 214 (10.34%) declared having a SpLDs, such as dyslexia (difficulty with reading), dysgraphia (difficulty with writing), dyspraxia (difficulty with coordination), or dyscalculia (difficulty with calculation).…”
mentioning
confidence: 99%
“…Their study sample included 2070 physicians, of whom 214 (10.34%) declared having a SpLDs, such as dyslexia (difficulty with reading), dysgraphia (difficulty with writing), dyspraxia (difficulty with coordination), or dyscalculia (difficulty with calculation). Botan and colleagues 1 found that physicians with SpLDs may have more difficulty with licensing examinations and assessments encountered throughout their training than learners without SpLDs. They therefore encouraged medical educators to understand the specific needs of learners with SpLDs and to accommodate these needs as part of ongoing assessment processes.…”
mentioning
confidence: 99%
See 2 more Smart Citations